Interactive learning framework for dynamic modeling and control of a flexible beam structure - Mat Darus, Intan Zaurah (2007)
The dynamic model represents the time–dependent aspects of a system. It is concerned with the temporal changes in the states of the objects in a system. The main concepts are: State, which is the situation at a particular condition during the lifetime of an object. Transition, a change in the state.